Effects of extraction methods and solvents on the bioactive compounds, antioxidant activity, and storage stability of anthocyanin rich blood fruit (Haematocarpus validus) extracts. Issue 5 (9th March 2021) - Sasikumar, Raju; Das, Dipak; Jaiswal, Amit Kumar
Abstract: The aim of the present study was to evaluate the efficient extraction technique and recovery of superior quality anthocyanins from blood fruit. Conventional and ultrasound‐assisted extraction techniques were carried out using different solvents. The results of the anthocyanin concentration, co‐pigmenting compounds, color values, and antioxidant activities of blood fruit extracts suggested that the methanol extract is better than the other solvents extract. The mass spectrometry detection of anthocyanins revealed the abundance of cyanidin‐3‐ O ‐glucoside (cy3g) fraction in ultrasonic methanol extract as compared with conventional extract. In the storage stability study, it was found that the stability of anthocyanins in acidic buffer was higher with low degradation rate as compared with that in the near neutral and alkaline buffer. The current study of anthocyanins rich blood fruit extract will enhance the utilization of this fruit in food and pharmaceutical industry to develop potential food colorants, antioxidants, cosmetics, and so forth. Practical applications: Natural colorants have been regarded as safe and alternatives to potentially harmful synthetic dyes, especially in food industries. The natural colorants including anthocyanins has increased due to their health‐promoting properties and an overall increase in consumer demand. It possesses industrially desirable attributes as they are attractive in color and hence have high consumer preference, soluble in water, exhibit moderate stability, and provide health/nutritional benefits. The extracted anthocyanins from blood fruits may help to use as a potent of natural coloring substance for food, nutraceutical, antioxidant, handicraft, pharmaceutical, and cosmetic industry.